Knowledge of Dental Students in Relation to Local Anesthetics and Associated Complications (International Journal of Medical and Surgical Sciences, 2015)
Local anesthesia is the most frequently performed procedure for all dentists and, despite their possible complications, often aspects such as dosage, contraindications and systemic effects are neglected. The objectives of this study are to evaluate prospectively the knowledge of undergraduate students for the technical, dosage and indication of local anesthetics in daily dental practice, in addition to clinical observation of possible complications from anesthesia. Questionnaires were distributed to students asking about the procedure undertaken, anesthetic volume used, because of the choice of the anesthetic, anesthetic dosage calculation, habit of relating the patient's weight dosage with the dosage being applied, habit of observing the reflux in cartridge in the anesthetic infiltration act and adverse effects on patients, type of anesthetic technique performed and expected time to onset of action of the drug. At the end of this study, we intend to be a greater awareness of students (undergraduates) about the systemic effects of local anesthetics in patients, and possibly decrease the expenses of the institution with excessive use of anesthetic cartridges arising from incorrect anesthetic technique. The vast majority of undergraduate students have no knowledge about the type of anesthesia to be used, the amount to be administered and the anesthetic action time. The awareness of students about the dosage of anesthetics and their systemic problems, reduces waste and the cost of the institution by the indiscriminate use of anesthetics, therebycontributing to improve the clinical management of students at graduation.